Compare outcome in patients of ileostomy and colostomy closure with surgical stapler versus ileostomy and colostomy closure with hand sewn anastomosis: a prospective study - Gohil, Vikram B.; Bhatt, Jenil Y.; Shah, Samir M.; Aphale, Rijuta (International Surgery Journal, 2020)
Background: Diverting temporary stoma is created to protect the primary bowel pathology and distal anastomosis. Once that primary pathology has been overcome or distal anastomosis gets healed, closure of temporary stomas can be carried out. Invention of stapling devices for intestinal anastomosis provided another dimension than hand sewn method to the stoma closure techniques. In this study, we have compared two methods of loop stoma closure-hand sewn method versus stapler method. Methods: This is prospective comparative study in which 50 cases of loop ileostomy/colostomy were taken. 25 patients underwent ileostomy/colostomy closure by hand sewn anastomosis (group A). Another 25 patients underwent ileostomy/colostomy closure by stapler anastomosis (group B). Time taken for operation, initiation of oral intake, anastomotic leak, post-operative wound infection and total hospital stay duration were compared between these two groups to conclude about which method is superior and in the best interest of patient and surgeon. Results: Mean operation time 105.96 minutes (group A) and 72.84 minutes (group B). Mean time to start oral intake 5.36 days (group A), 3.6 days (group B). 16% patients (4/25) group A and 4% patients (1/25) group B developed anastomotic leak. 28% patients (7/25) group A and 8% patients (2/25) group B had post-operative wound infection. Mean hospital stay 10.4 days in group A and 7.84 days in group B. Conclusions: Stapler method provides significant benefits in terms of less operative time, early oral intake and less hospital stay. Overall stapler method for stoma closure is more efficient and cost effective.